Global gene expression reveals an increase of HMGB1 and APEX1 proteins and their involvement in oxidative stress, apoptosis and inflammation pathways among beta‐thalassaemia intermedia and major phenotypes - Maia de Oliveira da Silva, João Pedro; Brugnerotto, Ana Flávia; S. Romanello, Karen; K. L. Teixeira, Karina; Lanaro, Carolina; S. Duarte, Adriana; G. L. Costa, Gustavo; da Silva Araújo, Aderson; C. Bezerra, Marcos André; de Farias Domingos, Igor; Pereira Martins, Diego A.; Malavazi, Iran; et al. (British journal of haematology, 2019)
Summary Beta‐thalassaemia (BT) is classified according to blood transfusion requirement as minor (BTMi), intermedia (BTI) and major (BTM). BTM is the most severe form, requiring regular transfusions while transfusion need is only occasional in BTI. Differential gene expression between patients has not been assessed so far. Here, we evaluated the global gene expression profiles during differentiation of human erythroid cells of two patients carrying the same mutation [CD39, (C → T)], though displaying different phenotypes (BTI and BTM). Considering the role of reactive oxygen species (ROS) in the pathophysiology of thalassaemia, we focused on differentially expressed genes involved in metabolic pathways triggered by ROS, such as inflammation and apoptosis, and, from these, we selected the Apurinic/Apyrimidinic Endodeoxyribonuclease 1 (APEX1) and High Mobility Group Box1 (HMGB1) genes, whose role in BT is not well established. An in‐depth expression analysis of transcriptional and protein levels in patients carrying a range of mutations associated with BT phenotypes indicated that APEX1 was increased in both BTI and BTM. Furthermore, higher amounts of HMGB1 was found in the plasma of BTI patients. Our findings suggest that these proteins have important roles in BT and could represent new targets for further studies aiming to improve the management of the disease.